Strategi Guru Sejarah dalam Mengintegrasikan Pembelajaran Sejarah Berbasis Kemampuan Berpikir Kritis di SMA Yogyakarta - Wulandari, Ana; Kumalasari, Dyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The problem found in the field is that HOTS or higher-order thinking Skills in Indonesia are not optimal. Teachers in schools are not fully prepared to implement assessments based on Higher-Order Thinking Skills. This study aims to analyze the strategy of integrating History learning based on higher-order thinking Skills in high schools throughout Yogyakarta. The study used a qualitative method with a descriptive approach. The research sample was selected sequentially from the principal, vice principal for curriculum, History subject teacher, and samples of grade X, XI, and XII students at SMA Negeri 3 Yogyakarta. Data collection techniques include observation, interviews, and documentation. Furthermore, data analysis was carried out using Miles, Huberman, and Saldana's data analysis techniques, namely collection, condensation, presentation, and conclusion. The results of the study showed that the HOTS integration strategy in high schools throughout Yogyakarta consisted of planning, implementation, and evaluation. Second, the obstacles to integrating HOTS-based learning are related to human resources, specifically the ability of teachers to integrate IT-based HOTS, time allocation with unbalanced discussion materials, and student's ability to comprehend diverse materials. Teachers responded by turning obstacles into opportunities. The impact of HOTS is studied from the cognitive, affective, and psychomotor domains. Each teacher has implemented unique and diverse teaching. The study's implications suggest that educational outcomes should prioritise the process and results of critical thinking, focusing on students who are knowledgeable and also morally and ethically intelligent.